1997
DOI: 10.1016/s0168-8278(97)80057-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ammonia and portal-systemic shunting on brain metabolism, neurotransmission and intracranial hypertension in hyperammonaemia-induced encephalopathy

Abstract: The effects of ammonia and portal-systemic shunting on brain metabolims, neurotransmission and intracranial hypertension in hyperammonaemia-induced encephalopathy Vogels, B.A.P.M.; van Steynen, B.; Maas, M.A.W.; Jorning, G.G.A.; Chamuleau, R.A.F.M. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
(34 reference statements)
3
17
2
1
Order By: Relevance
“…Cerebral GS, which is primarily localized in astrocytes [18], is believed preferentially to remove excess ammonia, and this leads to an increased concentration of glutamine in brain [9,33]. The present data show that treatment of glial cells with pathologically high ammonium concentrations for 3 h increases the intracellular glutamine concentration, and are in good accord with results from previous 1 H-NMR studies of acute hyperammonemia in human and rat brain [12][13][14][15]. After an ammonia load, the glutamate concentration transiently decreases in brain during hyperammonemia (see Cooper and Plum [9] for review), as it is consumed by glutamine synthesis, but recovers after 3 h [42,43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cerebral GS, which is primarily localized in astrocytes [18], is believed preferentially to remove excess ammonia, and this leads to an increased concentration of glutamine in brain [9,33]. The present data show that treatment of glial cells with pathologically high ammonium concentrations for 3 h increases the intracellular glutamine concentration, and are in good accord with results from previous 1 H-NMR studies of acute hyperammonemia in human and rat brain [12][13][14][15]. After an ammonia load, the glutamate concentration transiently decreases in brain during hyperammonemia (see Cooper and Plum [9] for review), as it is consumed by glutamine synthesis, but recovers after 3 h [42,43].…”
Section: Discussionsupporting
confidence: 91%
“…Since the brain lacks an effective urea cycle, cerebral ammonia removal relies mainly on glutamine formation in astrocytes [9,11]. High brain glutamine concentrations are commonly found in patients with hepatic encephalopathy as well as in induced hyperammonemia in the rat [12][13][14][15]. In contrast to the ammonia concentration [2,9,16], glutamine concentrations in the cerebrospinal fluid have been shown to correlate reasonably well with the clinical grade of hepatic encephalopathy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the time course of the ammonia-induced changes suggests some metabolic differences between primary and clonal glial cells, the correlation of Gln synthesis with intracellular osmolyte content and cell volume is obvious. The observed swelling of glioma cells already 3 h after ammonia treatment and the complementary rise in intracellular Gln with simultaneous release of organic osmolytes give further evidence for the role of Gln as an accumulated osmolyte in ammonia-induced brain edema, seen in acute HE [5][6][7][8][9][10]. The concept is supported by previous results from our laboratory, where both the increase in Gln and the decrease in the osmolyte content, induced by 3 h incubation with ammonia, were prevented in primary astrocytes and F98 glioma cells by administration of MSO, although cytosolic NH 4 + levels were elevated even more [22].…”
Section: Discussionmentioning
confidence: 73%
“…It may be due to a direct action of ammonia or due to metabolic alterations induced by high ammonia concentrations, such as increased activity of glutamine synthetase (GS), known to be enriched in astrocytes [4]. Increased ammonia entry into the brain is followed by an elevation of the brain glutamine (Gln) content in various brain regions, commonly found in patients with HE as well as induced HA in the rat [5][6][7][8][9][10]. It has been postulated that an osmotic effect due to intracellular Gln accumulation could mediate brain swelling and leads to brain edema in conditions associated with HA [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In different animal models, it has been consistently observed that infusion of ammonia can lead to accumulation of glutamine in the astrocytes, astrocytic swelling, increased brain water, and increased intracranial pressure. 5,8,40 It seems that mechanisms that counter-regulate astrocytic cell volume are too slow to compensate in the acute situation. 11,12 Recent research has identified a heterogeneous family of astrocytic glutamate receptors and transporters which regulate neuron-astrocytic trafficking of glutamate.…”
Section: Discussionmentioning
confidence: 99%